Ekrin porokarsinom: Nadir bir deri eki tümörünün iki farklı yüzü - (:unkn) unknown (My University, 2015)
Ekrin porokarsinom (EPK), ekrin ter bezlerinin intraepidermal duktal ünitelerinden kaynaklanan nadir bir malin deri eki tümörüdür. Klinik olarak birçok benin ve malin tümörü taklit edebilir. Burada farklı klinik ve histopatolojik özellikleri olan iki EPK olgusu sunulmaktadır. Her iki olguda tanı histopatolojik inceleme ile konulmuş ve tedavide total eksizyon ve greftlemeyle onarım uygulanmıştır

Eccrine porocarcinoma is a rare, malignant adnexal tumor arising from the intraepidermal ductal unit of the eccrine sweat glands. Clinically, it can mimic a variety of benign and malignant tumors. We report two patients who presented with different clinical and histopathological features. In both patients, the diagnosis was made after histopathological evaluation. Both patients underwent total excision with grafting
Eccrine porocarcinoma: Two faces of a rare adnexal tumor
Keywords: Dermatoloji